Analysis Of The Effects Of Attitude, Subjective Norms, and Perceived Behavioral Control On Consumer Purchase Intention Of Natural Gas For Vehicle With The Moderating Role Of Price Sensitivity - Ahmad Zakky Burhan; Janfry Sihite (Sultan Publisher, 2023)
This research aims to determine consumers purchase intention in using natural gas for vehicle with the moderating role of price sensitivity. This study used a quantitative approach in the form of a survey method. The population in this study consists of car users with fuel-powered vehicles located in the JABODETABEK area who have never owned a natural gas for vehicle before. The sample in this study consists of 122 car users with fuel-powered vehicles. Data processing is performed using the Partial Least Square (PLS) method. The results of this study indicate that attitude, perceived behavioural control, and price sensitivity have a significant influence on consumer purchase intention, while subjective norms do not have a significant influence. Price sensitivity also affects the relationship between subjective norms but does not affect the relationship between attitude and perceived behavioural control with consumer purchase intention. This study explores the impact of behaviour on purchase intention, emphasizing the management perspective. It reveals that positive attitudes towards environmentally friendly gas as an alternative fuel can be enhanced. The findings suggest that exogenous constructs moderately affect consumer purchase intention. Further research is needed to strengthen the influence of the dependent variable using additional variables.